OPTIMIZATION OF HANDLING NARCOTIC CRIMINAL ACTIONS PERFORMED BY CHILDREN THROUGH THE DIVERSION PROCESS - Sudirman Agus; M Taufik Makarao; Slamet Riyanto (Jurnal Hukum Jurisdictie, 2023)
Research on Optimizing the Handling of Narcotics Crimes Conducted by Children Through the Diversion Process aims to determine the diversion setting in the laws and regulations, to identify and analyze the implementation of diversion against children who are perpetrators of narcotics crimes based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, to find out what obstacles occur in handling child narcotics crimes in the diversion process. The approach that will be used is the empirical juridical/sociological juridical approach. In conducting the research, the writer will use descriptive analytical research method. The types of data used in this study are primary data and secondary data obtained from searching for definite data based on the results of data searches or interviews with parties concerned with this research and also from the literature. Methods of data collection using library research (Library Research). The data analysis method used is descriptive-qualitative analysis method. The results of this study are that diversion regulation in Indonesia begins with the idea of diversion in international law which is proclaimed in the SMRJJ (The Beijing Rules) as an international standard in the administration of juvenile criminal justice. 2012 on the Juvenile Criminal Justice System. The process of implementing the diversion carried out by investigators is guided by Article 7 paragraph (1) of Law no. 11 of 2012 concerning the Juvenile Criminal Justice System. As for the obstacles in the process of implementing the diversion of narcotics abuse crimes committed by children are: the lack of parental care will hinder the diversion process; lack of parental care also makes it difficult for investigators to obtain the child's identity; limited time for arresting children for the purpose of investigation; absence of parents; if what is caught is a homeless child, it will be difficult for investigators to obtain the identity of the child; lack of understanding of diversion efforts.